2021
DOI: 10.1007/s11116-021-10165-9
|View full text |Cite
|
Sign up to set email alerts
|

Scaling up cycling or replacing driving? Triggers and trajectories of bike–train uptake in the Randstad area

Abstract: The combined use of the bicycle and the train in the Netherlands has risen steadily over the past decade. However, little is yet known about the underlying processes driving the growth of bike–train use in the Netherlands. Are new bike–train trips replacing car trips, or are they primarily an extension of existing train travel and cycling practices? The present study investigates this question by exploring the main trajectories of bike–train uptake in the Randstad area. Following a mobility biographies approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…Comparing the coefficients shows that the use of Stadtbahn and buses increased bike use significantly only for residents in the metropolis, while the other spatial categories show a non-significant reduction. The symbiotic relationship between public transport and biking has been explored elsewhere ( Kager et al, 2016 , Nello-Deakin and te Brömmelstroet, 2021 ) and our research seems to confirm that there is indeed an interaction between these two transport modes. Further, reduced bus use increases car use particularly for residents of the medium-sized cities and urban areas.…”
Section: Resultssupporting
confidence: 82%
“…Comparing the coefficients shows that the use of Stadtbahn and buses increased bike use significantly only for residents in the metropolis, while the other spatial categories show a non-significant reduction. The symbiotic relationship between public transport and biking has been explored elsewhere ( Kager et al, 2016 , Nello-Deakin and te Brömmelstroet, 2021 ) and our research seems to confirm that there is indeed an interaction between these two transport modes. Further, reduced bus use increases car use particularly for residents of the medium-sized cities and urban areas.…”
Section: Resultssupporting
confidence: 82%
“…It is further argued that mobility is more habitual than reflected behavior and therefore needs more triggers than only self-induced motivation. Habits are more easily changed by “key events”, like workplace or residence changes and interventions, than only through values [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…A more logical explanation is that individuals who switch to a different class already show behaviours that fit with the class that they are moving to. Several studies found that people are more likely to adjust their attitudes to match their behaviour (e.g., Kroesen et al, 2017;; Nello-Deakin and Brömmelstroet, 2021;; van de Coevering et al, 2021). How do life events affect mode preferences and mode use over time of young adults?…”
Section: Main Conclusionmentioning
confidence: 99%